Multicolor emission based on amorphous-to-crystalline phase transitions in nanostructured Mn-doped glass. (1st November 2017) - Hoshino, Yoshinobu; Takahashi, Yoshihiro; Terakado, Nobuaki; Fujiwara, Takumi
Abstract: We fabricated glass-ceramics composed of emissive nanocrystals that show variation in photoluminescence coloration. The change in emission color is based on the amorphous-to-crystalline phase transformation in a Mn-containing zincogermanate glass. The transformation occurred at a 50 °C temperature range (538–588 °C), resulting in a change in photoluminescence color from orange to white to green. The color change is attributed to the co-crystallization of emissive nanophases and a change in the coordination state of Mn 2+ . Using laser-induced crystallization, we also achieved the space-selective arrangement of the different photoluminescence colors, indicating that photoluminescence coloration can be tuned in this Mn-doped glass.